The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1302/0301-620x.88b4.17195
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of anterior fracture-dislocations of the proximal humerus by open reduction and internal fixation

Abstract: Over a seven-year period we treated a consecutive series of 58 patients, 20 men and 38 women with a mean age of 66 years (21 to 87) who had an acute complex anterior fracture-dislocation of the proximal humerus. Two patterns of injury are proposed for study based upon a prospective assessment of the pattern of soft-tissue and bony injury and the degree of devascularisation of the humeral head. In 23 patients, the head had retained capsular attachments and arterial back-bleeding (type-I injury), whereas in 35 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 34 publications
3
78
2
4
Order By: Relevance
“…but there is no any significant difference in radiological and functional outcome in patients treated with either approach. Wu et al, [13] in his series of 63 patients found no statistically significant difference in clinical, radiographic, and electrophysiological outcomes between the deltopectoral approach and deltoid-splitting approach while surgical treatment of proximal humeral fractures. Hepp et al, [14] in his study observed better functional results with deltopectoral approach and concluded that choice of approach affects the functional outcome in management of proximal humeral fractures.…”
Section: Fig 1 Deltopectoral Approach Fig 2 Deltoid Split Lateral Appmentioning
confidence: 93%
“…but there is no any significant difference in radiological and functional outcome in patients treated with either approach. Wu et al, [13] in his series of 63 patients found no statistically significant difference in clinical, radiographic, and electrophysiological outcomes between the deltopectoral approach and deltoid-splitting approach while surgical treatment of proximal humeral fractures. Hepp et al, [14] in his study observed better functional results with deltopectoral approach and concluded that choice of approach affects the functional outcome in management of proximal humeral fractures.…”
Section: Fig 1 Deltopectoral Approach Fig 2 Deltoid Split Lateral Appmentioning
confidence: 93%
“…Fractures of the proximal humerus together with shoulder dislocation are important injuries because of both neurovascular injury risk and long-term high rates of complications (4). In this study, we presented the case of our patient with inferior shoulder dislocation and proximal humerus fracture together with right hip dislocation as well as acetabular and pertrochanteric fractures.…”
Section: Introductionmentioning
confidence: 94%
“…Avulsionsfrakturen (ossäre Bankart-Läsion) mit einer Fragmentgröße < 5 mm können gut toleriert werden [48] und werden oftmals nur bei konsekutiver Instabilität bevorzugt arthroskopisch refixiert [26]. Pfannenrandfrakturen ohne wesentliche Fragmentdislokation < 5 mm können mittels kurzer Ruhigstellung konservativ behandelt werden.…”
Section: Behandlung Und Prognoseunclassified
“…6 8 Anteriore Humeruskopfluxationsfraktur Typ 2 beim jungen Patienten, welcher trotz initialer intraoperativer Ischämie auch nach 12 Monaten ein gutes funktionelles Resultat ohne Kollaps zeigt bleiben. In der Arbeit von Robinson et al wird beschrieben, dass sich 3 von 7 Patienten mit Typ-2-Frakturen von der erfolgten ORIF ("open reduction internal fixation") weitgehend komplikationslos erholt haben [26]. Dies geht mit den Daten von Hertel et al einher, in welchen sich bei 8 von 10 initial ischämischen Humerusköpfen innerhalb von 5 Jahren kein Kollaps zeigte (.…”
Section: K Humerusunclassified
See 1 more Smart Citation